Assessing the Impact of Changes in Gender Equality on Female Homicide Victimization: 1980-2000. (April 2015) - Vieraitis, Lynne M.; Britto, Sarah; Morris, Robert G.
Numerous studies have tested the feminist hypothesis that gender inequality affects homicide rates by analyzing Census and Uniform Crime Report data for a single time period. Although these "snapshot" tests are important, they do not capture the "change" element that is implied by these hypotheses. According to feminist perspectives, gender inequality and gender equality could increase homicide rates, the former increasing the structural disadvantage of women relative to men and the latter representing a "backlash" effect. Women's absolute status may also be an important predictor of homicide victimization. Furthermore, it is quite possible that this process is dynamic and therefore the change in equality over time may be more important than the actual level of equality at any given time. The present study measures the impact of gender equality and women's absolute status on female homicide victimization using city-level data from 1980 to 2000. In general, the results suggest that changes in gender equality and women's absolute status have decreased women's rate of homicide victimization, and the negative effect of gender equality appears to have grown stronger over time; however, these results are not uniform across victim–offender relationships.